Epimeria (Pseudepimeria) debroyeri d'Acoz & Verheye 2017, sp. nov. - d'Acoz, Cédric d'Udekem; Verheye, Marie L. (Zenodo, 2017)
Epimeria ( Pseudepimeria ) debroyeri sp. nov. urn:lsid:zoobank.org:act: 05C0B30A-F5BD-40C0-A3FC-07DE05BFB375 Figs 265–271 Epimeria pulchra – Coleman 2007: 47, in part, colour plate 2 fig. f, not fig. 24a–b (= E. pulchra ). — Lörz & Coleman 2009: unnumbered photograph on p. 17. — Rauschert & Arntz 2015: 62, pl. 55, unnumbered photograph. non Epimeria pulchra Coleman, 1990a: 166–176, pls 10–16. Etymology The species is dedicated to Claude De Broyer (Royal Belgian Institute of Natural Sciences), who collected the holotype of the species. The name is a genitive. Type material Holotype RV Polarstern cruises: SOUTHERN OCEAN: large ♀, cruise PS14, ANT-VII/4, EPOS leg 3, stn 291 (GSN 14), eastern Weddell Sea, 71°06.1ʹ S, 12°33.5ʹ W to 71°05.9ʹ S, 12°34.8ʹ W, 499–515 m, bottom trawl, 19 Feb. 1989, coll. C. De Broyer (RBINS, INV. 132940). Description ROSTRUM. Long, overreaching tip of peduncle of antenna 1; in lateral view, anteriorly weakly curved in its middle and forming a blunt very obtuse angle with head, ventrally straight, tip abruptly curving downwards; in frontal view, fairly narrow, with weakly convex borders, with subacute tip. EYE. Medium-sized, conical. PEREION–PLEOSOME TOOTH PATTERN. Pereionite 1 with medium-sized broad and blunt-tipped mid-dorsal tooth pointing upwards of which the anterior border is straight and the posterior border is strongly convex, with pair of well-developed, blunt, dorsolateral teeth and pair of small ventrolateral teeth; pereionite 2 much narrower than pereionites 1 and 3, with small narrow blunt-tipped tooth pointing upwards (a bit shorter than mid-dorsal tooth of pereionite 1 and much shorter than mid-dorsal tooth of pereionite 3), with pair of small very blunt dorsolateral teeth, and pair of small ventrolateral teeth; pereionites 3–4 with large, broad and blunt to subangulate mid-dorsal tooth pointing upwards, of which the anterior and the posterior borders are both strongly convex, with pair of medium-sized, low and blunt dorsolateral teeth, and pair of small ...